2020
DOI: 10.1155/2020/2794036
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Clinically Important Difference of Gross Motor Function and Gait Endurance in Children with Motor Impairment: A Comparison of Distribution-Based Approaches

Abstract: Objective. The minimum clinically important difference (MCID) is a standard way of measuring clinical relevance. The objective of this work was to establish the MCID for the 6-minute walking test (6minWT) and the Gross Motor Function Measure (GMFM-88) in pediatric gait disorders. Methods. A cohort, pretest-posttest study was conducted in a hospitalized care setting. A total of 182 patients with acquired brain injury (ABI) or cerebral palsy (CP) performed 20 robot-assisted gait training sessions complemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 44 publications
1
46
2
Order By: Relevance
“…When physical therapy was subsequently resumed, the patient’s ability to maintain a sitting posture and weight-bearing capacity of the lower extremities were found to have decreased, and the Gross Motor Function Measure (GMFM-88) total score decreased from 34.5% to 31.9% ( Table 2 ). This decline in scores was more pronounced in the standing domain (dimension D) than in the other domains and was higher than the minimum clinically important difference (MCID) value of 5.2%, recently reported by Storm et al [ 12 ]. Specifically, the scores of items 53 to 55, related to the ability to maintain a standing position, decreased.…”
Section: Case Presentationcontrasting
confidence: 56%
“…When physical therapy was subsequently resumed, the patient’s ability to maintain a sitting posture and weight-bearing capacity of the lower extremities were found to have decreased, and the Gross Motor Function Measure (GMFM-88) total score decreased from 34.5% to 31.9% ( Table 2 ). This decline in scores was more pronounced in the standing domain (dimension D) than in the other domains and was higher than the minimum clinically important difference (MCID) value of 5.2%, recently reported by Storm et al [ 12 ]. Specifically, the scores of items 53 to 55, related to the ability to maintain a standing position, decreased.…”
Section: Case Presentationcontrasting
confidence: 56%
“…15 Minimum clinically important differences (MCIDs) of large effect size have been reported as ranging from 1.2 to 2.7 points for the GMFM-66 among ambulatory children with CP, 16 and it has been suggested that MCIDs may be even lower in more severely affected children. 17 The observed mean GMFM-66 improvement of 4.7 points exceeds this threshold, indicating a clinically significant improvement. Limitations of the study included its small sample size, the lack of a control group, and the single point of follow-up for efficacy (6 months) by the study team.…”
Section: Discussionmentioning
confidence: 88%
“…The GMFM‐66 is an accepted measure of motor function capability specific to CP and is highly recommended as a motor function outcome for CP research by the National Institute of Neurological Disorders and Stroke 15 . Minimum clinically important differences (MCIDs) of large effect size have been reported as ranging from 1.2 to 2.7 points for the GMFM‐66 among ambulatory children with CP, 16 and it has been suggested that MCIDs may be even lower in more severely affected children 17 . The observed mean GMFM‐66 improvement of 4.7 points exceeds this threshold, indicating a clinically significant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For this cohort of patients, the primary outcomes of interest were failure to achieve the MCID on the HOOS-PS, PROMIS PF-10a, and PROMIS M-10a. A change of PROM score from pre-to post-THA of 9.3 (HOOS-PS), 4.1 (PROMIS PF-10a), and 3.7 (PROMIS M-10a) were determined as the threshold for achieving MCID using the distribution-based method, a validated method that sets the MCID threshold as one-half of the standard deviation of PROM change from preoperative to postoperative states across all patients [16][17][18]. If the difference between the preoperative to postoperative PROM for a patient was higher than the MCID threshold, he or she was classified as having achieved the MCID.…”
Section: Introductionmentioning
confidence: 99%